The Implementation of the Inlislite Application System in Improving the Quality of Digital-Based Services at the Probolinggo City Public Library - Veronica Sri Astuti Nawangsih; Eko Yudianto Yunus; Dwi Prasetyo, Firmansyah (CV. Creative Tugu Pena, 2025)
This study explores the implementation of the INLISLite application system in enhancing the quality of digital-based services at the Public Library of Probolinggo City and examines the supporting and inhibiting factors influencing its application. Employing a descriptive qualitative approach, data were gathered through in-depth interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that INLISLite has effectively facilitated the transformation of library services toward digitalization, contributing to improved service quality. This improvement is reflected in the indicators of the DeLone & McLean Information Systems Success Model—system reliability, responsiveness, assurance, empathy, and tangible aspects—through features such as cataloging, membership management, circulation, digital guestbooks, OPAC, and reporting tools. However, several challenges persist, including limited IT-skilled personnel, unstable internet connectivity, and suboptimal reporting functionalities. Despite these obstacles, the implementation has been successful, driven by effective communication among librarians, users, and the Department of Communication and Information; the availability of adequate resources; adaptive and responsive staff attitudes; and a robust bureaucratic framework supported by clear standard operating procedures. In line with Edward III’s policy implementation theory, the study concludes that INLISLite plays a significant role in the modernization and efficiency of digital library services, although continued improvements in infrastructure and human resource capacity remain necessary.